Rancang Bangun Alat Pemilah Sampah Organik Dan Anorganik: Rancang Bangun Alat Pemilah Sampah Organik Dan Anorganik - Riza Alfita; Kunto Aji Wibisono; M.Wahid Anwar (Prodi Teknik Elektro Universitas PGRI Banyuwangi, 2021)
Garbage is one of the causes of a problem that is difficult to solve in Indonesia and even in other countries, many cities in Indonesia are filled with garbage. Maybe one of the factors is the scattering of garbage everywhere because humans themselves are lazy to throw away their place or are already accustomed to littering, causing rubbish to be scattered everywhere which can eventually lead to garbage pollution, unpleasant odors and ultimately can cause flooding. In this research, we will make a tool for sorting organic and inorganic waste, namely by making a tool such as a conveyor to sort the types of organic waste and the types of inorganic waste which will later be classified separately and collected in their own place so that they are not mixed together. To distinguish which organic and inorganic waste we will use a capacitive proximity sensor as a sorter, atmega 16 as a microcontroller to run all the work of the appliance system. DC motor as a conveyor drive. The LDR sensor detects the presence of waste. From the test, the organic and inorganic waste sorting tool has pretty good results with an average success rate of detecting organic waste of 66.67% and the success rate for inorganic waste is 63.33%.